Synthesis, characterization, crystal structure, and catalytic activity of palladium PEPPSI type complexes - Dusunceli, Serpil Demir; Gunel, Hayrunnisa; Keser, Serhat; Ozdemir, Namik; Ozdemir, Ismail (Elsevier, 2026)
Four novel Pd-PEPPSI complexes of p-cyano functionalized N-heterocyclic carbenes (NHC) [PdBr2(NHC)(L)], where NHC = 1-(2,3,5,6-tetramethylbenzyl)-3-(4-cyanobenzyl)benzimidazole-2-ylidene, 1,3-bis(4-cyanobenzyl) benzimidazole-2-ylidene, or 1-(4-methylbenzyl)-3-(4-cyanobenzyl)benzimidazole-2-ylidene, and L = pyridine or 3-chloropyridine were prepared and characterized by elemental analysis, 1H and 13C NMR, and IR spectroscopy. The molecular structure of dibromo[(1-(2,3,5,6-tetramethylbenzyl)-3-(4-cyanobenzyl)benzimidazole-2-ylidene] pyridinepalladium(II) (2a) was determined by single-crystal X-ray diffraction analysis. The catalytic activity of the Pd(II) complexes for Suzuki and Heck cross-coupling reactions was investigated in water-based solvent mixtures. They were moderately active in the reaction of phenylboronic acid and aryl bromides. With 4-bromoacetophenone and 4-bromobenzaldehyde, the desired products were obtained in 95% and 86% yields, respectively, within 15 min at 80 degrees C using dibromo [1,3-bis(4-cyanobenzyl) benzimidazole-2-ylidene]pyridine palladium(II), 2bIn the coupling of styrene with 4-bromoacetophenone, the product was obtained in 89% yield after 5 h 80 degrees C using catalyst 2a. The antioxidant activities of the four compounds were also evaluated using ABTS, OH and DPPH radical scavenging assays.
Keywords: Peppsi palladium complex; N-heterocyclic carbene; Catalysis; Cross coupling reaction; Aqueous medium; Antioxidant activity